![image](https://tex.z-dn.net/?f=%20y%28x%29%20%3D%20-%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%206x%20%2B%203%20%5C%5C%20y%27%28x%29%20%3D%20-%202x%20%2B%206%20%3D%200%20%5C%5C%20%3D%20%20%3E%20%20%20x_%7Bmax%20%7D%3D%203%20%5C%5C%20y_%7Bmax%20%7D%20%3D%20y%28x_%7Bmax%20%7D%29%20%3D%20%5C%5C%20%20%3D%20%20%20y%283%29%20%3D%20%20-%20%20%7B3%7D%5E%7B2%7D%20%20%2B%206%20%5Ccdot%203%20%2B%203%20%3D%20%20%5C%5C%20%20%3D%20%20-%209%20%2B%2018%20%2B%203%20%3D%2012)
x_{max }= 3 \\ y_{max } = y(x_{max }) = \\ = y(3) = - {3}^{2} + 6 \cdot 3 + 3 = \\ = - 9 + 18 + 3 = 12" alt=" y(x) = - {x}^{2} + 6x + 3 \\ y'(x) = - 2x + 6 = 0 \\ = > x_{max }= 3 \\ y_{max } = y(x_{max }) = \\ = y(3) = - {3}^{2} + 6 \cdot 3 + 3 = \\ = - 9 + 18 + 3 = 12" align="absmiddle" class="latex-formula">